Direct autotransfusion following emergency pericardiocentesis in patients undergoing cardiac electrophysiology procedures. (23rd April 2020) - Barbhaiya, Chirag R.; Guandalini, Gustavo S.; Jankelson, Lior; Park, David; Bernstein, Scott; Holmes, Douglas; Aizer, Anthony; Chinitz, Larry
Abstract: Introduction: Acute hemopericardium during cardiac electrophysiology (EP) procedures may result in significant blood loss and is the most common cause of procedure‐related death. Matched allogeneic blood is often not immediately available. The feasibility and safety of direct autotransfusion in cardiac electrophysiology patients requiring emergency pericardiocentesis is unknown. Methods: We retrospectively analyzed records of patients undergoing EP procedures at a single, tertiary care medical center who had procedure‐related acute hemopericardium requiring emergency pericardiocentesis during a 3‐year period. Procedure details, transfusion volumes, and clinical outcomes of patients who received direct autotransfusion of aspirated pericardial blood via a femoral venous sheath were compared to those of patients who did not receive direct autotransfusion. Results: During the study period, 10 patients received direct autotransfusion (group 1) and outcomes were compared with those of 14 control patients who did not receive direct autotransfusion (group 2). The volume of aspirated pericardial blood was similar in groups 1 and 2 (1.6 ± 0.7 L vs 1.3 ± 1.0 L, respectively; P  = .52). Amongst patients with aspirated volumes <1 L, group 1 patients (n = 4) were less likely than group 2 patients (n = 8) to require allotransfusion (0% vs 75%, P  = .02). Amongst patients with aspirated volume ≥1 L, group 1 patients (n = 6) required fewer units of red cell allotransfusion than group 2 patients (n = 6) (1.5 ± 0.8 units vs 4.3 ± 2.0 units, P  = .01). No procedural complications related to direct autotransfusion occurred. Conclusions: Direct autotransfusion following emergency pericardiocentesis during electrophysiology procedures requiring systemic anticoagulation is feasible and safe. The utilization of direct autotransfusion may eliminate or reduce the need for allotransfusion.